Preparation and Characterization of Cube-Like Magnesium Hydroxide by Gaseous Ammonia Bubbling - Li, Xue; Fan, Tianbo; Liu, Yunyi (Asian Journal of Chemistry, 2012)
Cube-like magnesium hydroxide nanoparticles were synthesized by ammonia gas (NH3) bubbling in the magnesium chloride (MgCl2) solution. The whole preparation did not require any modification such as hydrothermal treatment or surfactants. X-ray diffraction, scanning electron microscopy, laser particle size analyzer and thermo-gravimetric analyses have been employed to characterize these products. The influence of synthesis parameters on the magnesium hydroxide was investigated,such as types of base precipitants, reaction time and temperature. The growth mechanisms of magnesium hydroxide were also discussed.